Thermal Stability of Mayonnaise with Microparticulated Whey Protein-Pectin Complex as Fat Mimetics - Aisyah Wijayanti; Arima Diah Setiowati; Chusnul Hidayat (agriTECH, 2026)
Thermal stability remains a major challenge in low-fat oil-in-water emulsions, including mayonnaise, as reduced oil content weakens interfacial structure and increases susceptibility to droplet aggregation and phase separation during thermal processing. Although whey protein isolate (WPI)–pectin systems have been widely studied, the performance under thermal treatment, particularly when using microparticulated protein, remains insufficiently understood. Therefore, this study aimed to evaluate the application of microparticulated WPI–low-methoxyl pectin complexes as fat mimetics to improve the thermal and storage stability of low-fat mayonnaise. Two levels of fat replacement (30% and 60%) were formulated using different WPI:pectin ratios. The selected formulations were FM30 (30% fat mimetic; WPI:pectin = 1:3) and FM60 (60% fat mimetic; WPI:pectin = 1:10). The results showed that FM30 had superior thermal stability (>98%), smaller and more uniformly distributed droplets, as well as higher viscosity after thermal treatment at 70–90 °C. In contrast, FM60 showed greater droplet aggregation and reduced stability, particularly at elevated temperatures. Sensory evaluation indicated acceptable appearance, aroma, and taste for both low-fat formulations, although texture scores remained lower than the full-fat control. During 14-day storage at 30–50 °C, FM30 showed higher peroxide value (PV) and free fatty acid (FFA) formation compared to both FM60 and the full-fat formulation, indicating greater susceptibility to oxidative degradation. Despite the lower thermal stability, FM60 demonstrated relatively slower oxidation, reflecting differences in emulsion structure and oxidation kinetics. These results indicate that optimizing protein–polysaccharide balance is critical for achieving thermally stable low-fat emulsions. Although microparticulated WPI–pectin complexes show strong potential as fat mimetics, limitations in oxidative stability and texture suggest the need for further interfacial and formulation optimization.